THE EVALUATING METHOD OF THE CONTINUATION RELIABILITY OF THE CONSTRUCTION LIFE OF RAILWAY TRANSPORT OF THE CHERNOBYL NPP - Donchenko, A. V.; Khudiienko, V. A.; Sheleiko, T. V. (Science and Transport Progress, 2008)
A methodical approach to the reliability estimation and service life prolongation of the railway carrier vehicle design, included into the bulk container wagon TK-8, and intended for transportation of exhausted nuclear fuel by rail tracks of the alienation zone is described. The results of work performed and the analysis of real operation conditions are presented.